Optimalisasi Strategi Segmentation, Targeting dan Positioning dalam Meningkatkan Penjualan pada Mie Kirin Loe Gresik - Ferry Fahrial Rakhmad; Ety Dwi Susanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research was conducted on the basis of the rise of food and beverage businesses in Gresik Regency. The research methodology used uses a qualitative descriptive approach to determine segmentation, targeting and positioning strategies in increasing sales at the Kirin Loe Ramen Noodle business in Gresik. In collecting data, researchers carried out observations, in-depth interviews and documentation to identify segmentation, targeting and positioning of Mie Kirin Loe. Based on the results obtained by researchers, there are (1) Mie Kirin Loe segmentation including geographical, close to residential areas, near offices and industry, the demographic segment is 15-40 years old. The psychographic segment tends to be female ramen noodle consumers who have a consumptive nature and high curiosity, local people who like Padas. The consumer behavior segment wants low prices with the best product quality so that consumers are interested in coming back. (2) Targeting based on determining a responsive semi-selfservice pattern that prioritizes consumer comfort, sales potential focuses on UVP (Unique Value Product), media reach optimizes digital marketing through the Facebook, Instagram and Tiktok platforms. (3) Positioning based on attributes reflects Japanese culture starting from the logo, decoration and menu, based on the product category Kirin Loe Noodles offers a guarantee of quality, taste and uniqueness of the product that is different from others. Positioning with Japanese cultural nuances, according to price, Mie Kirin Loe adjusts prices to the specified target market and provides a varying price range from cheap to expensive.